Alcohol use severity and the neural correlates of the effects of sleep disturbance on sustained visual attention. (October 2021) - Li, Guangfei; Chen, Yu; Tang, Xiaoying; Li, Chiang-Shan R.
Abstract: Alcohol misuse is associated with sleep disturbance and cognitive dysfunction. However, the neural processes inter-relating the severity of alcohol use, sleep disturbance and cognitive performance remain under-investigated. We addressed this issue with a dataset of 964 subjects (504 women) curated from the Human Connectome Project. Participants were assessed with the Pittsburgh Sleep Quality Index (PSQI) and fMRI while identifying relational dimension pictures and matching dimension pictures (as a control) in alternating blocks. Imaging data were analyzed with published routines and the results were evaluated at a corrected threshold. Subjects showed lower accuracy rate and longer reaction time (RT) in relational than control blocks. The difference in RT between the two blocks (RTRel-Con ) was driven primarily by the RT and correlated positively with performance accuracy of relational trials, suggesting that a more cautious response (i.e., longer RTRel-Con ) improved accuracy. The severity of alcohol use, identified from principal component analysis of drinking metrics, was positively correlated with sleep disturbance. Further, whole-brain regression identified activity of the superior colliculus (SC) during relational vs. control blocks in positive and negative correlation with RTRel-Con and PSQI score, respectively. Mediation and path analyses demonstrated a significant model: more severe alcohol use → greater sleep disturbance → diminished SC activity → impaired performance. These findings support the influences of alcohol misuse on sleep and suggest neural correlates that mediate the relationship between sleep disturbance and altered sustained attention in young adults.